PENDAPATAN PETANI DARI BUDIDAYA TANAMAN PURIK (Mitragyna sp) DI DESA NANGA MANDAY KECAMATAN BIKA KABUPATEN KAPUAS HULU - Oktaviani, Hilaria Dita; Muin, Sudirman; Hardiansyah, Gusti (JURNAL HUTAN LESTARI, 2020)
Purik (Mitragyna sp), is one of the forestry plants that is currently cultivated and is the livelihood of the community, especially in Nanga Manday Village, Bika District, Kapuas Hulu Regency, when rubber prices dropped and fish catches were uncertain. The purpose of this study to answer how much the level of income, the value of the R / C ratio, Break Ivent Point (BEP) of production and prices as well as the factors that affect the level of community income. The methodology used is observation and structured interviews. Based on data analysis, the community income from Purik cultivation is Rp 10,658 / kg with an R / C ratio of 3.6 (>1) and the value of production BEP of 15.66 kg and the price BEP of Rp. 1,231 / kg. Based on the results of multiple linear regression analysis of income (profit) purik cultivation business as follows: Å¶ = 1.012 - 0.021X1 + 0.000X2 - 0.0004X3 + 0.006X4 - 1.090X5 - 1.107X6 - 0.011D with the results of the analysis determining the R Square number is .986 (98%).Keywords: income, Nanga Manday,Â purik cultivation